Effect of Solid State Fermentation with Whey on Nutrient Composition of Pomegranate Peel Supplemented Sunflower Meal: Effect of Fermentation on Nutritional Value of Sunflower Meal - Dumlu, B; Bölükbaşı , ŞC (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of the study is to improve the nutritional value of sunflower meal by solid state fermentation (SSF) using agricultural wastes such as whey and pomegranate peel. Experiment was conducted with six groups. First group SM (sunflower meal) + TW (tap water), the second group SM + W (whey), the third group SM + W + 0.5% PP, the fourth group SM + W + 1% PP, the fifth group SM + W + 1.5% PP and the sixth group SM + W + 2% PP, respectively. The mixtures were prepared to complete 100 grams of sunflower meal with 0, 0,5, 1,0, 1,5 and 2,0 grams of pomegranate peel (PP), respectively. Each group consisted of eight replicates. Prepared mixtures were placed in 500 ml erlenmayers and 120 ml tap water was added to the mixing of first group and 120 ml whey was added in other groups and then mixed homogeneously. Four of the erlenmayers prepared for each group without being fermented were dried at room temperature. The remaining erlenmayers were fermented in 32°C±2 for 48 hours. Dry matter, crude protein, ether extract, crude ash, crude fiber, phytic acid ratios and phytase activities, antioxidant activities and yeast (Saccharomyces cerevisiae) numbers were determined in fermented and non-fermented feed samples. As a result of solid state fermentation with whey by adding pomegranate peel to sunflower meal, crude protein ratio, antioxidant activity and yeast count increased, and phytic acid ratio decreased. In conclusion, sunflower meal with functional properties was obtained. In addition, wastes such as whey and pomegranate peel were used as feed and environmental pollution was prevented. Keywords: Sunflower meal; pomegranate peel; whey; solid state fermentation; functional meal